2012
DOI: 10.1002/ibd.21916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exclusive enteral nutrition on body composition and circulating micronutrients in plasma and erythrocytes of children with active Crohnʼs disease

Abstract: Lean but not fat mass improved at the end of EEN. Median concentrations for several plasma micronutrients improved on EEN but carotenoids were depleted. These findings may have implications for clinical practice and producers of enteral feeds. As plasma concentrations for many micronutrients can be affected by the acute phase response, measurements in erythrocytes may be a better marker of actual body stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Although it is believed that adults with CD have higher REE than the general population, 21 a recent study by Filippi et al 22 showed that adults with CD in remission had similar REE/FFM to healthy controls. Second, remission was induced by various therapeutic approaches, such as EN, 23 prednisolone, IFX, 18 or surgery, 10 which might have a different impact on REE and body composition. However, the strength of the current study was that it was the first to examine dynamically the change of metabolism and body composition in different disease states of adult CD.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is believed that adults with CD have higher REE than the general population, 21 a recent study by Filippi et al 22 showed that adults with CD in remission had similar REE/FFM to healthy controls. Second, remission was induced by various therapeutic approaches, such as EN, 23 prednisolone, IFX, 18 or surgery, 10 which might have a different impact on REE and body composition. However, the strength of the current study was that it was the first to examine dynamically the change of metabolism and body composition in different disease states of adult CD.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of before/after mucosal microbiota studies impacts our understanding of the fundamental biological mechanism of action of exclusive enteral nutrition, with most work to date relying on serial faecal samples instead. Exclusive enteral nutrition also helps with nutritional rehabilitation and lean body mass, hence is an obvious choice in paediatric inflammatory bowel disease practice where weight loss is a common feature at presentation . Use of exclusive enteral nutrition within adult practice remains limited and probably relates to the cumbersome social aspects of a liquid‐only diet.…”
Section: Microbiota As a Therapeutic Target In Inflammatory Bowel Dismentioning
confidence: 99%
“…We retrospectively collected clinical, anthropometric, and laboratory data from the electronic database and clinical records at the time of diagnosis, at the time of remission (week [6][7][8][9][10][11][12], and at the time of relapse, or at the end of observation when the patient was still in remission. National references have been used for Z score calculations [27].…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous studies have demonstrated short-term EEN efficacy with better side effect profile [6] improved growth velocity, weight gain, lean body mass, and bone health [6][7][8][9][10][11][12][13]. On the basis of such evidence demonstrating efficacy and other beneficial effects, EEN is considered a first-line induction therapy in pediatric CD [14].…”
Section: Introductionmentioning
confidence: 99%